Claudia Poll's Full Stroke at 120 m of Her 200 m Gold Medal Race at the 1998 Perth World Championships - Rudhall, B. S.
Video pictures (18 frames) and the appropriate technical/ biomechanical explanations for Claudia Poll's full stroke at 120 m of her 200 m gold medal race at the 1998 Perth World Championships. Claudia Poll's stroke displays a classic two-beat kick. The arm movement of this stroke is somewhat like that of Brooke Bennett and Janet Evans in that there is no lost time after entry in attempting to develop propulsion. The stroke is completed rapidly, a full cycle lasting 1.1 seconds. Streamlining is maintained well. The positioning of the hand/forearm-propelling surface in propulsion is worthy of emulation.